Cape FARIANA Hotel - SAMARA, AWS (My University, 2020)
In search for adventure and natural beauty, tourists have started exploring very valuable and usually highly sensitive environments. As a response to these activities a traditional approach of implementing accommodations and touristic facilities follows to meet the needs of visitors, but the fact that its untouched and undeveloped natural environments is what makes it special and a destination to this kind of tourism. It is the role of planers, designers and operators of these developments to make it possible for tourists to experience nature through beautiful architecture and with the very minimum impact on site, making it the least visually and environmentally damaging. It is the purpose of this thesis to set up suggestions when making architecture to function as accommodations for tourists in natural environments. The importance of resort planning process and its effects on the image of the resort destination will be studied.